Numerical Simulation of Heat Transfer Problem in Hot and Cold Rolling Process (Journal of Engineering, 2006)
An efficient numerical model had been developed to model the thermal behaviour of the rolling process. An Eulerian formulation was employed to minimize the number of grid points required. The model is capable to calculate the temperature distribution, the heat penetration depth, the convection heat transfer coefficient of cooling, the flow of metal through the roll gap, and the heat generation by plastic deformation and friction. The roll is assumed to rotate at constant speed, and the temperature variations are assumed to be cyclically steady state and localized with a very thin layer near the surface. The Conventional Finite Difference (CFDM) based on cylindrical coordinates was used to model the roll, and a Generalized Finite Difference Method (GFDM) with non-orthogonal mesh was employed in the deformed strip region and the roll-strip interface area. An upwind differencing scheme was selected to overcome the numerical instability resulting from the high velocity ( high Peclet number ) involved in the rolling process. The equations of the strip and roll are then coupled together and solved simultaneously. Both cold and hot rolling heat transfer behaviours, velocity distribution, and heat generation by deformation and friction under typical rolling conditions were presented to demonstrate the feasibility and capability of the developed numerical model. It has been found that, while the strip is under deformation, the bulk temperature inside the strip increases continuously; this is largely controlled by the deformation energy. On the other hand, the strip surface temperature changes much more drastically and it is mainly controlled by the friction heat and the roll temperature. The roll acts like a heat sink, because the coolant heavily cools it. Thus, as soon as the strip hits the roll its surface temperature drops. Since considerable friction and deformation heat are created along the interface and transferred from the neighboring sub-layer, the surface temperature picks up rapidly. Finally, the results of the temperature distribution for both cold and hot rolling and the heat generation by deformation and friction obtained from the present study were compared with previous published work to verify the validity of the numerical solution. Good acceptable agreements were obtained.